SCIENTIFIC DISCOURSES OF PROFESSOR FLORIJ BATSEVYCH: До ювілею Флорія Сергійовича - NIKA, Oksana; SAZONOVA, Yaroslava (Linguistic and Conceptual Worldviews, 2024)
The article outlines the main research ideas of Professor Florij Batsevych, which have become relevant in modern communicative studies, linguistic pragmatics, and linguistic narratology. The analysis is made in accord with the main spheres of Professor’s studies: the research of estranged artistic texts, literary prosaic texts of Ukrainian and foreign authors, oral speech and memorata, research on text theory and text-discursive categories, and discursive markers. The authors of the article focus on the integrity of the linguist’s scientific conception, which is manifested in the interrelationships of the multifaceted research on text, discourse, speech genre, in the development of new scientific directions in linguistics, and the search for scientific perspectives. Prospective innovations in Florij Batsevych’s scientific output, which represent the study of language/speech in the communicative-cognitive paradigm, are analyzed and reveal the linguist’s own theoretical views and their practical implementation on various language material. Among other Professor’s ideas, it is worth mentioning the development of deviatology as a linguistic-pragmatic sub-discipline, keen interest to texts created in altered states of consciousness, absurd texts, texts as the reflection of some traumatic experience, family communication, etc.; particular attention is paid to minor but important elements of discursive-pragmatic speech organization (e.g., particles, which he classifies as discourse markers) because classical structuralist approach to their investigation, in F. Batsevych’s point of view, does not reveal all the value of these components in the creation of new senses.The authors conclude that the specificity of Professor’s scientific output lies in the nature of his view on language and its research – anthropocentricity and humanism.
Keywords: the scientific output of Florij Batsevych, relevance of research ideas, linguistic pragmatics, linguistic narratology, communicative studies